Critical Discourse in Contemporary Management Science - Sułkowski, Łukasz; Zawadzki, Michał (Folia Philosophica, 2018)
The article presents characteristic features of the critical approach in management—Critical Management Studies—which keeps gaining popularity in the global management studies discourse. The authors point out the major paradigmatic assumptions of this line of inquiry, its intellectual sources and its critical tools, emphasizing in particular the role of education as the key to effective emancipation. The article closes with a criticism of CMS, which falls into line with the demand of the critical approach that the practice of scientific research should be accompanied by autocriticism.